Behavioural and Biological Effects of a Mediterranean-Based Diet in Postpartum Mice and Prenatally Stressed Mice Offspring - Udechukwu, Maryann (Université d'Ottawa | University of Ottawa, 2024)
Physiological changes in the perinatal period may increase the risk for postpartum mental disturbances. In the offspring, this risk for mental disorders may be compounded by adversities experienced by the mother during pregnancy. Alterations in inflammatory and neurotrophic factors, barrier function, and microbiota composition in the brain and/or intestinal environments have been suggested to underlie some of these mental disturbances in postpartum mothers and prenatally stressed offspring. The past years have seen a bloom of studies showing that dietary patterns based on the Mediterranean (Med) diet were associated with better mental health, reduced levels of systemic pro-inflammatory markers, and increased gut bacteria with health benefits in the intestinal tract. This thesis examined, in mice, whether a Med-based diet improved the behaviours of postpartum dams and prenatally stressed offspring. Pro-inflammatory cytokines, brain-derived neurotrophic factor (BDNF), and tight junctions in brain and intestinal samples as well as gut microbiota metrics were also determined. Considering the sex biases in the outcomes of prenatal stress and the prevalence of depression and anxiety, sex differences in the effects of prenatal stress and the Med-based diet were investigated in the offspring. In Study 1, we examined behaviour and biological markers in brain and intestinal samples in postpartum dams fed a Control or a Med-based diet from preconception through early postpartum and showed that in addition to increasing self-care behaviour, the Med-based diet reduced pro-inflammatory cytokines and increased BDNF and claudin-5 in the hippocampus. Study 2 examined whether the Med-based diet limited socioemotional deficits and biological changes promoted by a prenatal stressor in neonatal offspring and showed that although it did not mitigate the reductions in vocalizations in stressed pups, the diet limited the cytokine increases and the BDNF decreases in the hippocampus and/or prefrontal cortex of these pups, particularly in females. Study 2 also looked at anxiety- and depressive-like behaviours and biological markers in adult offspring subjected to the same manipulations as in the neonatal pups and showed that the Med-based diet limited the stress-induced increases in anxiety-like behaviours, hippocampal and colonic pro-inflammatory cytokines, and changes in gut microbiota composition, again particularly in females. Overall, this thesis demonstrates the potential of Med-based dietary patterns to support maternal and offspring's (particularly in female offspring) mental health, possibly by modulating inflammatory processes, neuroplasticity, and gut microbiota.
Keywords: postpartum; prenatal stress; diet; Mediterranean diet; sex; mental health; gut microbiota; inflammation; brain; early-life; development; neurotrophic factors; tight junctions; maternal health; offspring health; behaviour